PERTIMBANGAN DETERMINAN PEMILIHAN CHANNEL DISTRIBUSI DALAM MENGHADAPI PEMASARAN MENDATANG - Widiastuti, Imron (Fakultas Teknik Universitas Wisnuwardhana, 2014)
Most producers do not sell their goods directly to the their final users. Between them stands a set of intermediaries performing a variety of functions. These inter-mediaries constitute a marketing channel. Some intermediaries- such as mer-chants, the agents, and facilitators assist in the distribution process. Marketing channels are sets of interdependent organizations involved in the process of making product or service available for use or consumption. Thus, the amrketing-channel decisions are among the most critical decisions facing the management. The channels chosen directly affect all the other marketing deci-sions, such as pricing and advertising. The small and new firm typically start as a local operation selling in a limited market. It is different when firm do mass production and complex custo-mers, the efficiency is a matter to deliver good to users. The succesfull firm that served in wide market, sometime employed a different channel in defferent market. Thus, controllability and adaptability is another important matters to decide the channel-design. The latest economy showed the increasing importance of electronic com-merce, it makes essential to develop a theory of virtual value chain. The on-line marketing becomes emerging for the decade. The support of developed technology of internet and telecommunication change some theory of tradisional marketing